NO MORE DEBATES ABOUT PARODY. HERE IS THE TRANSPARODY! CHANGING THE TRADITIONAL TERMINOLOGY THROUGH HORROR COMICS - Koukoulas, Yannis; Missiou, Marianna (Design/Arts/Culture, 2025)
The concept and content of parody have been studied extensively in literature and to a large extent in the visual arts. A common practice of art theorists and historians, critics, cultural analysts, etc., is to identify intertextual and interpictorial correlations between works and to attempt to classify artistic intentions and methods into taxonomic categories based on older terminologies. The complex parodies of comics, however, in which texts and images are combined and iconic works of art become the subject of a new critique of the “old”, may require a new terminology to describe them. Taking the covers of horror comics series Crossed: Family Values and Raise the Dead as examples and tracing in them the interpictorial relationship they develop with well-known visual works of the past, the need to adopt a new terminology is highlighted and the term “transparody” is proposed as being able to encompass this new kind of textual and visual parody that comics achieve.